Impact of body composition on vitamin D requirements in healthy adults with vitamin D deficiency - Dai, Dexing; Ling, Yali; Xu, Feng; Li, Haibo; Wang, Rui; Gu, Yingying; Xia, Xuedi; Xiong, An; Sun, Ruoman; Qiu, Lei; Ding, Ya; Yu, Yixin; et al. (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have shown that individuals with high body mass index typically require high doses of vitamin D supplementation to correct vitamin D deficiency. However, it is unclear which specific body composition is the determining factor affecting the bioavailability of vitamin D after supplementation. The aim of this study was to determine which body components affect the bioavailability of vitamin D.MethodsIn order to ensure the compliance of the study subjects and avoid the impact of sunlight on vitamin D3 levels, the subjects received multiple intramuscular (i.m.) injections of vitamin D2 until their serum levels of 25-hydroxyvitamin D [25(OH)D] were above 30 ng/mL. All subjects received two i.m. injections of 600,000 IU vitamin D2, and dose adjustments were made every 6 weeks based on whether serum 25(OH)D levels were sufficient. The levels of serum 25(OH)D2 and 25(OH)D3 were determined by liquid chromatography tandem mass spectrometry. The body composition was measured using dual-energy X-ray absorptiometry and corrected using body fat mass index (FMI). Based on the 100% difference in 25(OH)D levels before and after vitamin D supplementation, the sample size was calculated, and 20 subjects would provide over 95% of the power to show the difference.ResultsAfter two dose adjustment, the serum 25(OH)D levels of all subjects were above 30 ng/mL. The subjects were divided into ≤ 1,200,000 IU vitamin D2 (n=10) and ≥ 2,400,000 IU vitamin D2 (n=15) based on the i.m. dose of vitamin D2. The results showed that compared with subjects receiving ≤ 1,200,000 IU vitamin D2, subjects receiving ≥ 2,400,000 IU of vitamin D2 had a higher total body fat mass index (FMI), particularly with higher trunk fat content and high visceral adipose tissue mass. However, the dosage of vitamin D2 supplementation was not related to BMI and lean mass content.ConclusionThe body fat content, especially trunk fat content, is the main body component that affects the bioavailability of vitamin D in healthy adults. Healthy adults with high trunk fat content have low bioavailability of vitamin D and require relatively high dose of vitamin D to achieve sufficient levels.Clinical Trial Registrationhttp://www.chictr.org.cn, identifier ChiCTR2300070641.